Magnetic Sm-BFO and Ce-BFO nanoflakes as protective coating layers for C-steel in acidic chloride environments. (January 2019) - Khalaf, Mai M.; El-Lateef, Hany M. Abd; Farghal, G.; Ibrahim, E.M.M.
Graphical abstract: Highlights: Ce- and Sm-doped BFO nanoflakes were synthesized by sol-gel method. The steel substrate was coated by the dip coating process. Effect of the number of layers and surfaces morphology of Ce-and Sm-BFO nanoflakes were examined. It was found that the steel corrosion can be controlled by coating with Ce-and Sm-BFO nanoflakes. The Sm-BFO nanoflakes film has the highest protection compared to that of Ce-BFO nanoflakes. Abstract: This investigation suggests a straightforward method for the C-steel coating by two different doped BiFeO3 (BFO) nanomaterials, specifically Ce and Sm doped BFO nanoflakes for protection against corrosion. The Ce and Sm doped BFO nanoflakes were prepared by sol–gel process and the C-steel was coated by the dip coating method. Influences of the number of layers and surfaces morphology of Ce-and Sm-BFO nanoflakes on the corrosion resistance of coated C-steel were studied. Different techniques such as FT-IR; X-ray diffraction and scanning electron microscopy were performed in order to describe the coatings structure. Moreover, the electrical and magnetic properties were also examined. Electrochemical impedance spectroscopy (EIS) and potentiodynamic measurements (PDP) were utilized to investigate the corrosion protection execution in HCl solution. Both samples are weak ferromagnetic ordering and have a semiconductor feature. It was found that the C-steel corrosion can be controlled by coating with Ce-and Sm-BFO nanoflakes. The corrosion protection results indicated that the efficiency of Sm-BFO nanoflakes as a corrosion protective material is very high compared to that of Ce-BFO nanoflakes due to the smooth surface of Sm-BFO and rough mesoporous surface of Ce-BFO as shown in SEM results.